On ageing, economization of health, and media ethics: how much is a month of life worth? - Młoźniak, Iwona; Zatoński, Mateusz (Journal of Health Inequalities, 2018)
This article explores the complex intersection of public health issues, media responsibility, and determinants of policymaking. In particular, it considers the problematic nature of the attempts to monetise life expectancy in the public debate in Poland. While calculating pensions on the base of the expected lifespan of citizens is a widely accepted economic practice, it is methodologically fraught, and ethically controversial to use the same measures in reporting the problem of premature mortality in national media. This article emphasises the necessity of taking a holistic and comprehensive approach to public health issues both by the media, and by policymakers. Referring to the Health in All Policies (HiAP) framework the authors argue that population health is a crucial factor shaping sustainable socio-economic developments in Poland and the quality of life of its citizens.